2008
DOI: 10.1161/hypertensionaha.107.106062
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Wave Reflections and Arterial Stiffness in Normal Pregnancy as Assessed by Applanation Tonometry

Abstract: Abstract-Normal pregnancy is associated with profound alterations in the maternal cardiovascular system. The aim of the present study was to assess noninvasively, using applanation tonometry, the maternal central aortic blood pressures (BP), effects of wave reflection and arterial stiffness (aortic and brachial pulse wave velocity) in normal pregnancy. This was a cross sectional study including 193 women with normal singleton pregnancies at 11 to 41 weeks of gestation and 23 nonpregnant controls, matched for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
62
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 37 publications
(40 reference statements)
13
62
2
2
Order By: Relevance
“…There are many studies showing similar results using central artery compliance by invasive procedures (mean arterial pressure, aortic augmentation index (AIx) and central systolic blood pressure (SBP) [7,13] and non invasive techniques (MRI and USG) [14,15]. But contrary to our study some of the studies have not shown change in peripheral arterial compliance during different phases of menstrual cycle [7,16]. …”
Section: Resultscontrasting
confidence: 77%
“…There are many studies showing similar results using central artery compliance by invasive procedures (mean arterial pressure, aortic augmentation index (AIx) and central systolic blood pressure (SBP) [7,13] and non invasive techniques (MRI and USG) [14,15]. But contrary to our study some of the studies have not shown change in peripheral arterial compliance during different phases of menstrual cycle [7,16]. …”
Section: Resultscontrasting
confidence: 77%
“…Our findings support two recent studies, which addressed normal values of cSBP and AIx throughout pregnancy. 19,20 Furthermore, we found that AIx-75, but not cSBP, was independent of bSBP throughout pregnancy. Our present data suggested that measurement of cSBP and AIx might offer additional information about maternal arterial compliance, which might be impaired in various obstetric complications such as preeclampsia.…”
Section: Discussionmentioning
confidence: 55%
“…17 In addition, women with a history of earlyonset preeclampsia and intrauterine growth restriction were reported to exhibit increased AIx even 6 to 24 months postpartum. 18 Although two recent studies addressed normal values of cSBP and AIx throughout pregnancy showing its nadir in mid-pregnancy, 19,20 their physiological aspects in healthy pregnant individuals, such as their relationships to brachial blood pressure, are currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…27 Our findings of a rise in arterial stiffness from the second trimester to term and postnatally are supportive of previous studies using brachial-ankle PWV as a composite measure of systemic and central stiffness 28 and augmentation index. 29 Other studies report no change in PWV with gestation 30 or a general decrease in PWV and augmentation index during pregnancy. 6,8,9,11 All of these studies had limited and wide time points, with the third-trimester visits performed earlier than in our study.…”
Section: Discussionmentioning
confidence: 99%